Modification method of high-carbon-yield asphalt for prebaked anode
By distilling and heat-treating coal tar pitch, combined with the optimization of modified boron nitride agents and additives, the problems of insufficient strength, conductivity and high-temperature stability of prebaked anode products were solved, and a coordinated improvement in performance was achieved.
Patent Information
- Application Number
- CN202511130891.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-13
- Publication Date
- 2025-11-11
AI Technical Summary
Existing asphalt modification methods result in prebaked anode products with poor strength, poor conductivity, and insufficient high-temperature stability, which limits their application efficiency.
Coal tar pitch is distilled and heat-treated, combined with modified boron nitride and additives. The performance of the pitch is optimized by preheating, heating and ultrasonic impregnation of the modified boron nitride, as well as acid solution activation and ball milling of the additives.
This improved the strength, conductivity, and high-temperature stability of prebaked anode products, achieving coordinated performance improvements and enhanced stability.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of prebaked anode technology, and more specifically to a method for modifying prebaked anodes with high residual carbon content asphalt. Background Technology
[0002] In the aluminum electrolysis industry, prebaked anodes are key components, and their performance directly affects the energy consumption, production efficiency, and product quality of the electrolysis process. Asphalt, as an important binder for prebaked anodes, plays a decisive role in the structural stability and conductivity of the anode under high-temperature electrolysis conditions due to its residual carbon content.
[0003] Existing asphalt modification methods are relatively simple, and the modification processes are still in place. The asphalt obtained for reuse as prebaked anode products has poor strength and conductivity, as well as poor high-temperature stability, which limits the product's efficiency. Summary of the Invention
[0004] In view of the deficiencies of the prior art, the purpose of this invention is to provide a method for modifying prebaked anodes with high residual carbon content asphalt, so as to solve the problems mentioned in the background art.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] This invention provides a method for modifying prebaked anode pitch with high residual carbon content, comprising the following steps:
[0007] Step 1: Distill coal tar pitch at 300-350℃ for 10 minutes, then vacuum dry the distilled pitch at 120-150℃, and then heat treat it under nitrogen at 380-420℃ for 3 hours. After treatment, the matrix material is obtained.
[0008] Step 2: Add 10-15% of the total amount of modified boron nitride agent and 8-12% of the total amount of additive to the matrix material and mix evenly. Finally, heat treat for 1 hour.
[0009] Preferably, the temperature of the heat treatment is 450-500℃.
[0010] Preferably, the modified boron nitride agent is prepared by:
[0011] S1: Stir boron nitride in a potassium permanganate solution that is 5-8 times the total amount of boron nitride, then wash with water, filter, and dry.
[0012] The dry boron nitride was preheated at 155-160℃ for 1 hour, then heated to 255℃ at a rate of 2-5℃ / min and held for 5-8 minutes. Finally, it was air-cooled to room temperature to obtain pretreated boron nitride.
[0013] S2: The pretreated boron nitride is impregnated in an impregnation solution of 7-11 times the total amount of pretreated boron nitride and ultrasonically impregnated. After impregnation, the mixture is filtered and dried to obtain the modified boron nitride agent.
[0014] Preferably, the ultrasonic impregnation treatment has an impregnation power of 350-400W and an impregnation time of 1 hour; the mass fraction of the potassium permanganate solution is 5-8%.
[0015] Preferably, the impregnation solution is prepared by:
[0016] S2a: Nanocellulose, silane coupling agent KH550 and ethanol aqueous solution are mixed evenly in a weight ratio of 4:1:7 to obtain nanocellulose solution; 3-5 parts of zinc oxide whiskers, 2-4 parts of lanthanum oxide and 5-8 parts of nanocellulose solution are mixed evenly to obtain whisker modified solution.
[0017] S2b: Mix 2-3 parts of bismuth titanate, 1-3 parts of sodium dodecylbenzenesulfonate, 5-8 parts of α-alumina and 4-7 parts of sodium silicate solution evenly to obtain a hybrid agent;
[0018] The hybrid agent and whisker modification solution were mixed and ball-milled at a weight ratio of (4-5):9. After ball milling, the mixture was filtered and dried to obtain the impregnation solution.
[0019] Preferably, the mass fraction of the ethanol aqueous solution is 75-85%; the mass fraction of the sodium silicate solution is 5-8%; and the ball milling speed for the blending ball milling treatment is 1000-1500 r / min, and the ball milling time is 2 h.
[0020] Preferably, the additive is prepared by:
[0021] The nano-mica powder was stirred thoroughly in a sufficient amount of acid solution, then washed with water, filtered, and dried. The dried nano-mica powder and the additive solution were ball-milled at a weight ratio of 7:5 at a speed of 1000-1500 r / min for 2 hours. After the ball milling was completed, the powder was filtered and dried to obtain the additive.
[0022] Preferably, the acid solution has a mass fraction of 4-7%.
[0023] Preferably, the preparation method of the additive solution is as follows: 3-5 parts of β-cyclodextrin, 1-2 parts of titanate coupling agent, 2-3 parts of nano-silicon wafers, 5-8 parts of sodium lignosulfonate solution, and 3-5 parts of basalt fiber.
[0024] Preferably, the sodium lignosulfonate solution has a mass fraction of 5-8%.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] This invention relates to a high carbon residue asphalt modification process using coal tar pitch that undergoes distillation followed by heat treatment. The process involves blending with modified boron nitride and additives, as well as thermal optimization. The resulting asphalt, when modified and used in prebaked anode products, exhibits excellent strength, conductivity, and high-temperature stability, achieving a synergistic improvement in product performance. The modified boron nitride agent is preheated and then heated to optimize its activity. Further improvements include ultrasonic impregnation with an impregnation solution, ball milling of the hybrid agent and whisker-modifying solution, and blending of bismuth titanate, α-alumina, and other raw materials in the hybrid agent with the whisker-modifying solution. Through blending and optimization, the zinc oxide whiskers, lanthanum oxide, and nanocellulose liquid in the whisker modification solution are improved in synergy, and the raw materials are blended and optimized. The resulting modified boron nitride agent optimizes the performance coordination and stability of the product in the system. The additives are improved by activating nanomica powder with acid solution, and then ball milling is optimized in combination with the additives. The β-cyclodextrin, titanate coupling agent, nanosilicon wafers, and basalt fibers in the additive solution are blended and optimized. The blending and synergistic combination of nanosilicon wafers and basalt fibers is optimized and improved. The resulting additives further enhance the functionality of the product in the system, thereby further improving the product's performance. Detailed Implementation
[0027] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] This embodiment of a method for modifying prebaked anode pitch with high residual carbon content includes the following steps:
[0029] Step 1: Distill coal tar pitch at 300-350℃ for 10 minutes, then vacuum dry the distilled pitch at 120-150℃, and then heat treat it under nitrogen at 380-420℃ for 3 hours. After treatment, the matrix material is obtained.
[0030] Step 2: Add 10-15% of the total amount of modified boron nitride agent and 8-12% of the total amount of additive to the matrix material and mix evenly. Finally, heat treat for 1 hour.
[0031] The heat treatment temperature in this embodiment is 450-500℃.
[0032] The preparation method of the modified boron nitride agent in this embodiment is as follows:
[0033] S1: Stir boron nitride in a potassium permanganate solution that is 5-8 times the total amount of boron nitride, then wash with water, filter, and dry.
[0034] The dry boron nitride was preheated at 155-160℃ for 1 hour, then heated to 255℃ at a rate of 2-5℃ / min and held for 5-8 minutes. Finally, it was air-cooled to room temperature to obtain pretreated boron nitride.
[0035] S2: The pretreated boron nitride is impregnated in an impregnation solution of 7-11 times the total amount of pretreated boron nitride and ultrasonically impregnated. After impregnation, the mixture is filtered and dried to obtain the modified boron nitride agent.
[0036] In this embodiment, the ultrasonic impregnation treatment uses an impregnation power of 350-400W and an impregnation time of 1 hour; the mass fraction of the potassium permanganate solution is 5-8%.
[0037] The method for preparing the impregnation solution in this embodiment is as follows:
[0038] S2a: Nanocellulose, silane coupling agent KH550 and ethanol aqueous solution are mixed evenly in a weight ratio of 4:1:7 to obtain nanocellulose solution; 3-5 parts of zinc oxide whiskers, 2-4 parts of lanthanum oxide and 5-8 parts of nanocellulose solution are mixed evenly to obtain whisker modified solution.
[0039] S2b: Mix 2-3 parts of bismuth titanate, 1-3 parts of sodium dodecylbenzenesulfonate, 5-8 parts of α-alumina and 4-7 parts of sodium silicate solution evenly to obtain a hybrid agent;
[0040] The hybrid agent and whisker modification solution were mixed and ball-milled at a weight ratio of (4-5):9. After ball milling, the mixture was filtered and dried to obtain the impregnation solution.
[0041] In this embodiment, the mass fraction of the ethanol aqueous solution is 75-85%; the mass fraction of the sodium silicate solution is 5-8%; and the ball milling speed for the blending ball milling treatment is 1000-1500 r / min, and the ball milling time is 2 h.
[0042] The preparation method of the additive in this embodiment is as follows:
[0043] The nano-mica powder was stirred thoroughly in a sufficient amount of acid solution, then washed with water, filtered, and dried. The dried nano-mica powder and the additive solution were ball-milled at a weight ratio of 7:5 at a speed of 1000-1500 r / min for 2 hours. After the ball milling was completed, the powder was filtered and dried to obtain the additive.
[0044] The mass fraction of the acid solution in this embodiment is 4-7%.
[0045] The preparation method of the additive solution in this embodiment is as follows: 3-5 parts of β-cyclodextrin, 1-2 parts of titanate coupling agent, 2-3 parts of nano-silicon wafers, 5-8 parts of sodium lignosulfonate solution, and 3-5 parts of basalt fiber.
[0046] The sodium lignosulfonate solution in this embodiment has a mass fraction of 5-8%.
[0047] Example 1.
[0048] This embodiment of a method for modifying prebaked anode pitch with high residual carbon content includes the following steps:
[0049] Step 1: Distill coal tar pitch at 300℃ for 10 minutes, then vacuum dry the distilled pitch at 120℃, and then heat treat it under nitrogen at 380℃ for 3 hours. After treatment, the matrix material is obtained.
[0050] Step 2: Add 10% of the modified boron nitride agent and 8% of the additive to the matrix material and mix evenly. Finally, heat treat for 1 hour.
[0051] The heat treatment temperature in this embodiment is 450°C.
[0052] The preparation method of the modified boron nitride agent in this embodiment is as follows:
[0053] S1: Stir boron nitride in a potassium permanganate solution that is 5 times the total amount of boron nitride, then wash with water, filter, and dry.
[0054] The dried boron nitride was preheated at 155℃ for 1 hour, then heated to 255℃ at a rate of 2℃ / min, held for 5 minutes, and finally air-cooled to room temperature to obtain pretreated boron nitride.
[0055] S2: The pretreated boron nitride is impregnated in an impregnation solution with a volume of 7 times the total amount of pretreated boron nitride and ultrasonically impregnated. After impregnation, the mixture is filtered and dried to obtain the modified boron nitride agent.
[0056] In this embodiment, the ultrasonic impregnation treatment uses an impregnation power of 350W and an impregnation time of 1 hour; the mass fraction of the potassium permanganate solution is 5%.
[0057] The method for preparing the impregnation solution in this embodiment is as follows:
[0058] S2a: Nanocellulose, silane coupling agent KH550 and ethanol aqueous solution are mixed evenly in a weight ratio of 4:1:7 to obtain nanocellulose solution; 3 parts zinc oxide whiskers, 2 parts lanthanum oxide and 5 parts nanocellulose solution are mixed evenly to obtain whisker modified solution.
[0059] S2b: Mix 2 parts of bismuth titanate, 1 part of sodium dodecylbenzenesulfonate, 5 parts of α-alumina and 4 parts of sodium silicate solution evenly to obtain a hybrid agent;
[0060] The hybrid agent and whisker modification solution were mixed and ball-milled at a weight ratio of 4:9. After ball milling, the mixture was filtered and dried to obtain the impregnation solution.
[0061] In this embodiment, the mass fraction of the ethanol aqueous solution is 75%; the mass fraction of the sodium silicate solution is 5%; and the ball milling speed for the blending ball milling treatment is 1000 r / min, and the ball milling time is 2 h.
[0062] The preparation method of the additive in this embodiment is as follows:
[0063] The nano-mica powder was stirred thoroughly in a sufficient amount of acid solution, then washed with water, filtered, and dried. The dried nano-mica powder and the additive solution were ball-milled at a weight ratio of 7:5 at a speed of 1000 r / min for 2 hours. After the ball milling was completed, the powder was filtered and dried to obtain the additive.
[0064] The mass fraction of the acid solution in this embodiment is 4%.
[0065] The preparation method of the additive solution in this embodiment is as follows: 3 parts β-cyclodextrin, 1 part titanate coupling agent, 2 parts nano-silicon wafers, 5 parts sodium lignosulfonate solution, and 3 parts basalt fiber.
[0066] The sodium lignosulfonate solution in this embodiment has a mass fraction of 5%.
[0067] Example 2.
[0068] This embodiment of a method for modifying prebaked anode pitch with high residual carbon content includes the following steps:
[0069] Step 1: Distill coal tar pitch at 350℃ for 10 minutes, then vacuum dry the distilled pitch at 10℃, and then heat treat it under nitrogen at 420℃ for 3 hours. After treatment, the matrix material is obtained.
[0070] Step 2: Add 15% of the modified boron nitride agent and 8-12% of the additives to the matrix material and mix evenly. Finally, heat treat for 1 hour.
[0071] The heat treatment temperature in this embodiment is 500°C.
[0072] The preparation method of the modified boron nitride agent in this embodiment is as follows:
[0073] S1: Stir boron nitride in potassium permanganate solution (8 times the total amount of boron nitride) until fully mixed, then wash with water, filter, and dry.
[0074] The dried boron nitride was preheated at 160℃ for 1 hour, then heated to 255℃ at a rate of 5℃ / min and held for 8 minutes. Finally, it was air-cooled to room temperature to obtain pretreated boron nitride.
[0075] S2: The pretreated boron nitride is impregnated in an impregnation solution with a volume of 11 times the total amount of pretreated boron nitride and ultrasonically impregnated. After impregnation, the mixture is filtered and dried to obtain the modified boron nitride agent.
[0076] In this embodiment, the ultrasonic impregnation treatment uses an impregnation power of 400W and an impregnation time of 1 hour; the mass fraction of the potassium permanganate solution is 8%.
[0077] The method for preparing the impregnation solution in this embodiment is as follows:
[0078] S2a: Nanocellulose, silane coupling agent KH550 and ethanol aqueous solution are mixed evenly in a weight ratio of 4:1:7 to obtain nanocellulose solution; 5 parts zinc oxide whiskers, 4 parts lanthanum oxide and 8 parts nanocellulose solution are mixed evenly to obtain whisker modified solution.
[0079] S2b: Mix 3 parts of bismuth titanate, 3 parts of sodium dodecylbenzenesulfonate, 8 parts of α-alumina and 7 parts of sodium silicate solution evenly to obtain a hybrid agent;
[0080] The hybrid agent and whisker modification solution were mixed and ball-milled at a weight ratio of 5:9. After ball milling, the mixture was filtered and dried to obtain the impregnation solution.
[0081] In this embodiment, the mass fraction of the ethanol aqueous solution is 85%; the mass fraction of the sodium silicate solution is 8%; and the ball milling speed for the blending ball milling treatment is 1500 r / min, and the ball milling time is 2 h.
[0082] The preparation method of the additive in this embodiment is as follows:
[0083] The nano-mica powder was stirred thoroughly in a sufficient amount of acid solution, then washed with water, filtered, and dried. The dried nano-mica powder and the additive solution were ball-milled at a weight ratio of 7:5 at a speed of 1500 r / min for 2 hours. After the ball milling was completed, the powder was filtered and dried to obtain the additive.
[0084] The mass fraction of the acid solution in this embodiment is 7%.
[0085] The preparation method of the additive solution in this embodiment is as follows: 5 parts β-cyclodextrin, 2 parts titanate coupling agent, 3 parts nano-silicon wafers, 8 parts sodium lignosulfonate solution, and 5 parts basalt fiber.
[0086] The sodium lignosulfonate solution in this embodiment has a mass fraction of 8%.
[0087] Example 3.
[0088] This embodiment of a method for modifying prebaked anode pitch with high residual carbon content includes the following steps:
[0089] Step 1: Distill coal tar pitch at 325℃ for 10 minutes, then vacuum dry the distilled pitch at 135℃, and then heat treat it under nitrogen at 400℃ for 3 hours. After treatment, the matrix material is obtained.
[0090] Step 2: Add 12.5% of the total amount of modified boron nitride agent and 10% of the total amount of additive to the matrix material and mix evenly. Finally, heat treat for 1 hour.
[0091] The heat treatment temperature in this embodiment is 455°C.
[0092] The preparation method of the modified boron nitride agent in this embodiment is as follows:
[0093] S1: Stir boron nitride in a potassium permanganate solution that is 6.5 times the total amount of boron nitride, then wash with water, filter, and dry;
[0094] The dried boron nitride was preheated at 158℃ for 1 hour, then heated to 255℃ at a rate of 3.5℃ / min and held for 6.5 minutes. Finally, it was air-cooled to room temperature to obtain pretreated boron nitride.
[0095] S2: The pretreated boron nitride is impregnated in an impregnation solution with a total amount of 9 times the pretreated boron nitride and ultrasonically impregnated. After impregnation, the mixture is filtered and dried to obtain the modified boron nitride agent.
[0096] In this embodiment, the ultrasonic impregnation treatment uses an impregnation power of 375W and an impregnation time of 1 hour; the mass fraction of the potassium permanganate solution is 6.5%.
[0097] The method for preparing the impregnation solution in this embodiment is as follows:
[0098] S2a: Nanocellulose, silane coupling agent KH550 and ethanol aqueous solution are mixed evenly in a weight ratio of 4:1:7 to obtain nanocellulose solution; 4 parts zinc oxide whiskers, 3 parts lanthanum oxide and 6.5 parts nanocellulose solution are mixed evenly to obtain whisker modified solution.
[0099] S2b: 2.5 parts bismuth titanate, 2 parts sodium dodecylbenzenesulfonate, 6.5 parts α-alumina and 5 parts sodium silicate solution are mixed evenly to obtain a hybrid agent;
[0100] The hybrid agent and whisker modification solution were mixed and ball-milled at a weight ratio of 4.5:9. After ball milling, the mixture was filtered and dried to obtain the impregnation solution.
[0101] In this embodiment, the mass fraction of the ethanol aqueous solution is 80%; the mass fraction of the sodium silicate solution is 6.5%; and the ball milling speed for the blending ball milling treatment is 1250 r / min, and the ball milling time is 2 h.
[0102] The preparation method of the additive in this embodiment is as follows:
[0103] The nano-mica powder was stirred thoroughly in a sufficient amount of acid solution, then washed with water, filtered, and dried. The dried nano-mica powder and the additive solution were ball-milled at a weight ratio of 7:5 at a speed of 1250 r / min for 2 hours. After the ball milling was completed, the powder was filtered and dried to obtain the additive.
[0104] The mass fraction of the acid solution in this embodiment is 5.5%.
[0105] The preparation method of the additive solution in this embodiment is as follows: 4 parts β-cyclodextrin, 1.5 parts titanate coupling agent, 2.5 parts nano-silicon wafers, 6.5 parts sodium lignosulfonate solution, and 4 parts basalt fiber.
[0106] The sodium lignosulfonate solution in this embodiment has a mass fraction of 6.5%.
[0107] Example 4.
[0108] This embodiment of a method for modifying prebaked anode pitch with high residual carbon content includes the following steps:
[0109] Step 1: Distill coal tar pitch at 310℃ for 10 minutes, then vacuum dry the distilled pitch at 130℃, and then heat treat it under nitrogen at 390℃ for 3 hours. After treatment, the matrix material is obtained.
[0110] Step 2: Add 12% of the modified boron nitride agent and 8-12% of the additives to the matrix material and mix evenly. Finally, heat treat for 1 hour.
[0111] The heat treatment temperature in this embodiment is 460°C.
[0112] The preparation method of the modified boron nitride agent in this embodiment is as follows:
[0113] S1: Stir boron nitride in a potassium permanganate solution that is 6 times the total amount of boron nitride, then wash with water, filter, and dry.
[0114] The dried boron nitride was preheated at 156℃ for 1 hour, then heated to 255℃ at a rate of 3℃ / min and held for 6 minutes. Finally, it was air-cooled to room temperature to obtain pretreated boron nitride.
[0115] S2: The pretreated boron nitride is impregnated in an impregnation solution with a volume of 8 times the total amount of pretreated boron nitride and ultrasonically impregnated. After impregnation, the mixture is filtered and dried to obtain the modified boron nitride agent.
[0116] In this embodiment, the ultrasonic impregnation process uses an impregnation power of 360W and an impregnation time of 1 hour; the mass fraction of the potassium permanganate solution is 6%.
[0117] The method for preparing the impregnation solution in this embodiment is as follows:
[0118] S2a: Nanocellulose, silane coupling agent KH550 and ethanol aqueous solution are mixed evenly in a weight ratio of 4:1:7 to obtain nanocellulose solution; 4 parts zinc oxide whiskers, 3 parts lanthanum oxide and 6 parts nanocellulose solution are mixed evenly to obtain whisker modified solution.
[0119] S2b: Mix 2 parts bismuth titanate, 2 parts sodium dodecylbenzenesulfonate, 6 parts α-alumina and 5 parts sodium silicate solution evenly to obtain a hybrid agent;
[0120] The hybrid agent and whisker modification solution were mixed and ball-milled at a weight ratio of 5:9. After ball milling, the mixture was filtered and dried to obtain the impregnation solution.
[0121] In this embodiment, the mass fraction of the ethanol aqueous solution is 77%; the mass fraction of the sodium silicate solution is 6%; and the ball milling speed for the blending ball milling treatment is 1100 r / min, and the ball milling time is 2 h.
[0122] The preparation method of the additive in this embodiment is as follows:
[0123] The nano-mica powder was stirred thoroughly in a sufficient amount of acid solution, then washed with water, filtered, and dried. The dried nano-mica powder and the additive solution were ball-milled at a weight ratio of 7:5 at a speed of 1150 r / min for 2 hours. After the ball milling was completed, the powder was filtered and dried to obtain the additive.
[0124] The mass fraction of the acid solution in this embodiment is 5%.
[0125] The preparation method of the additive solution in this embodiment is as follows: 4 parts β-cyclodextrin, 1 part titanate coupling agent, 2 parts nano-silicon wafers, 6 parts sodium lignosulfonate solution, and 4 parts basalt fiber.
[0126] The sodium lignosulfonate solution in this embodiment has a mass fraction of 6%.
[0127] Comparative Example 1.
[0128] Unlike Example 3, no modified boron nitride agent was added.
[0129] Comparative Example 2.
[0130] Unlike Example 3, no impregnation solution was added during the preparation of the modified boron nitride agent.
[0131] Comparative Example 3.
[0132] Unlike Example 3, no hybrid agent was added to the impregnation solution.
[0133] Comparative Example 4.
[0134] Unlike Example 3, bismuth titanate and α-alumina were not added to the hybrid agent.
[0135] Comparative Example 5.
[0136] Unlike Example 3, zinc oxide whiskers and lanthanum oxide were not added to the impregnation solution.
[0137] Comparative Example 6.
[0138] Unlike Example 3, no additives were added.
[0139] Comparative Example 7.
[0140] Unlike Example 3, no nano-silicon wafers and basalt fibers were added to the additive solution.
[0141] The strength, electrical conductivity, and high-temperature stability of the products in Examples 1-4 and Comparative Examples 1-7 were tested. The test results are as follows:
[0142]
[0143] As can be seen from Examples 1-4 and Comparative Examples 1-7, the product of the present invention can achieve coordinated improvement in compressive strength, electrical conductivity and high temperature resistance.
[0144] The product's performance deteriorates significantly if neither the modified boron nitride agent nor one of the additives is added. The product's performance is most significantly improved when both are combined in a synergistic manner.
[0145] In the preparation of modified boron nitride, no impregnation solution was added, no hybrid agent was added to the impregnation solution, no bismuth titanate and α-alumina were added to the hybrid agent, no zinc oxide whiskers and lanthanum oxide were added to the impregnation solution, and no nano-silicon wafers and basalt fibers were added to the additive solution. The performance of the products tended to deteriorate. Only the product raw materials obtained by the method of this invention have the most significant performance effect. Furthermore, the impregnation solution of this invention is unique, and the effect of using other raw materials and methods to replace it is not as significant as that of this invention.
[0146] The innovation of this invention lies in:
[0147] The modified boron nitride agent is made by preheating and then raising the temperature to improve the activity of boron nitride. It is further improved by ultrasonic impregnation in an impregnation solution, and by ball milling the hybrid agent and whisker modifying solution in the impregnation solution. The hybrid agent, including bismuth titanate and α-alumina, is blended and optimized with the whisker modifying solution. The whisker modifying solution contains zinc oxide whiskers, lanthanum oxide, and nanocellulose solution, which work synergistically. The optimized blending of raw materials results in a modified boron nitride agent that improves the performance coordination and stability of the product within the system. The additive is made by activating nano-mica powder with an acid solution and then ball milling it. The additive solution contains β-cyclodextrin, titanate coupling agent, nano-silicon wafers, and basalt fibers, which are then blended and optimized. The blending and synergistic blending of nano-silicon wafers and basalt fibers further enhances the functionality of the product within the system, thus improving its performance.
[0148] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
[0149] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A method for modifying prebaked anode pitch with high residual carbon content, characterized in that, Includes the following steps: Step 1: Distill coal tar pitch at 300-350℃ for 10 minutes, then vacuum dry the distilled pitch at 120-150℃, and then heat treat it under nitrogen at 380-420℃ for 3 hours. After treatment, the matrix material is obtained. Step 2: Add 10-15% of the total amount of modified boron nitride agent and 8-12% of the total amount of additive to the matrix material and mix evenly. Finally, heat treat for 1 hour.
2. The method for modifying prebaked anode pitch with high residual carbon content according to claim 1, characterized in that, The heat treatment temperature is 450-500℃.
3. The method for modifying prebaked anode pitch with high residual carbon content according to claim 1, characterized in that, The preparation method of the modified boron nitride agent is as follows: S1: Stir boron nitride in a potassium permanganate solution that is 5-8 times the total amount of boron nitride, then wash with water, filter, and dry. The dry boron nitride was preheated at 155-160℃ for 1 hour, then heated to 255℃ at a rate of 2-5℃ / min and held for 5-8 minutes. Finally, it was air-cooled to room temperature to obtain pretreated boron nitride. S2: The pretreated boron nitride is impregnated in an impregnation solution of 7-11 times the total amount of pretreated boron nitride and ultrasonically impregnated. After impregnation, the mixture is filtered and dried to obtain the modified boron nitride agent.
4. The method for modifying prebaked anode pitch with high residual carbon content according to claim 3, characterized in that, The ultrasonic impregnation treatment uses an impregnation power of 350-400W and an impregnation time of 1 hour; the mass fraction of the potassium permanganate solution is 5-8%.
5. The method for modifying prebaked anode pitch with high residual carbon content according to claim 3, characterized in that, The method for preparing the impregnation solution is as follows: S2a: Nanocellulose, silane coupling agent KH550 and ethanol aqueous solution are mixed evenly in a weight ratio of 4:1:7 to obtain nanocellulose solution; 3-5 parts of zinc oxide whiskers, 2-4 parts of lanthanum oxide and 5-8 parts of nanocellulose solution are mixed evenly to obtain whisker modified solution. S2b: Mix 2-3 parts of bismuth titanate, 1-3 parts of sodium dodecylbenzenesulfonate, 5-8 parts of α-alumina and 4-7 parts of sodium silicate solution evenly to obtain a hybrid agent; The hybrid agent and whisker modification solution were mixed and ball-milled at a weight ratio of (4-5):
9. After ball milling, the mixture was filtered and dried to obtain the impregnation solution.
6. The method for modifying prebaked anode pitch with high residual carbon content according to claim 5, characterized in that, The ethanol aqueous solution has a mass fraction of 75-85%; the sodium silicate solution has a mass fraction of 5-8%; the ball milling speed for the blending ball milling treatment is 1000-1500 r / min, and the ball milling time is 2 h.
7. The method for modifying prebaked anode pitch with high residual carbon content according to claim 1, characterized in that, The preparation method of the additive is as follows: The nano-mica powder was stirred thoroughly in a sufficient amount of acid solution, then washed with water, filtered, and dried. The dried nano-mica powder and the additive solution were ball-milled at a weight ratio of 7:5 at a speed of 1000-1500 r / min for 2 hours. After the ball milling was completed, the powder was filtered and dried to obtain the additive.
8. The method for modifying prebaked anode pitch with high residual carbon content according to claim 7, characterized in that, The acid solution has a mass fraction of 4-7%.
9. A method for modifying prebaked anode pitch with high residual carbon content according to claim 7, characterized in that, The preparation method of the additive solution is as follows: 3-5 parts β-cyclodextrin, 1-2 parts titanate coupling agent, 2-3 parts nano-silicon wafers, 5-8 parts sodium lignosulfonate solution, and 3-5 parts basalt fiber.
10. A method for modifying prebaked anode pitch with high residual carbon content according to claim 9, characterized in that, The sodium lignosulfonate solution has a mass fraction of 5-8%.